Bioprinting-based automated deposition of single cancer cell spheroids into oxygen sensor microelectrode wells. Issue 22 (18th October 2022) - Dornhof, Johannes; Zieger, Viktoria; Kieninger, Jochen; Frejek, Daniel; Zengerle, Roland; Urban, Gerald A.; Kartmann, Sabrina; Weltin, Andreas
Abstract : With an advanced bioprinter, we print cancer cell spheroids directly into chip-based oxygen microsensors to determine single spheroid metabolism and drug responses. Abstract : Three-dimensional (3D) cell agglomerates, such as microtissues, organoids, and spheroids, become increasingly relevant in biomedicine. They can provide in vitro models that recapitulate functions of the original tissue in the body and have applications in cancer research. For example, they are widely used in organ-on-chip systems. Microsensors can provide essential real-time information on cell metabolism as well as the reliability and quality of culture conditions. The combination of sensors and 3D cell cultures, especially single spheroids, is challenging in terms of reproducible formation, manipulation, and access to spheroids, precise positioning near sensors, and high cell-to-volume ratios to obtain meaningful biosignals in the most parallel approach possible. To overcome this challenge, we combined state-of-the-art bioprinting techniques to automatically print tumour spheroids directly into microwells of a chip-based electrochemical oxygen sensor array. We demonstrated highly accurate and reproducible spheroid formation (diameter of approx. 200 μm) and a spheroid deposition precision of 25 μm within a volume of 22 nl per droplet. Microstructures and hydrogel-coated microwells allowed the placement of single MCF-7 breast cancer spheroids close to the sensor electrodes. The microelectrode wells were sealed for oxygen measurements within a 55 nl volume for fast concentration changes. Accurate and stable amperometric oxygen sensor performance was demonstrated from atmospheric to anoxic regions. Cellular respiration rates from single tumour spheroids in the range of 450–850 fmol min −1 were determined, and alterations of cell metabolism upon drug exposure were shown. Our results uniquely combine bioprinting with 3D cell culture monitoring and demonstrate the much-needed effort for facilitation, parallelization, sensor integration, and drug delivery in 3D cell culture and organ-on-chip experiments. The workflow has a high degree of automation and potential for scalability. In order to achieve greater flexibility in the automation of spheroid formation and trapping, we employed a method based on drop-on-demand liquid handling systems, instead of the typical on-chip approach commonly used in microfluidics. Its relevance ranges from fundamental metabolic research over standardization of cell culture experiments and toxicological studies, to personalized medicine, e.g. patient-specific chemotherapy.